Enhancement of motor learning by focal intermittent theta burst stimulation (iTBS) of either the primary motor (M1) or somatosensory area (S1) in healthy human subjects - Platz, Thomas; Adler-Wiebe, Marija; Roschka, Sybille; Lotze, Martin (Restorative neurology and neuroscience, 2018)
Motor rehabilitation after brain damage relies on motor re-learning as induced by specific training. Non-invasive brain stimulation (NIBS) can alter cortical excitability and thereby has a potential to enhance subsequent training-induced learning. Knowledge about any priming effects of NIBS on motor learning in healthy subjects can help to design targeted therapeutic applications in brain-damaged subjects. To examine whether complex motor learning in healthy subjects can be enhanced by intermittent theta burst stimulation (iTBS) to primary motor or sensory cortical areas. Eighteen young healthy subjects trained eight different arm motor tasks (arm ability training, AAT) once a day for 5 days using their left non-dominant arm. Except for day 1 (baseline), training was performed after applying an excitatory form of repetitive transcranial magnetic stimulation (iTBS) to either (I) right M1 or (II) S1, or (III) sham stimulation to the right M1. Subjects were randomly assigned to conditions I, II, or III. A principal component analysis of the motor behaviour data suggested eight independent motor abilities corresponding to the 8 trained tasks. AAT induced substantial motor learning across abilities with generalisation to a non-trained test of finger dexterity (Nine-Hole-Peg-Test, NHPT). Participants receiving iTBS (to either M1 or S1) showed better performance with the AAT tasks over the period of training compared to sham stimulation as well as a bigger improvement with the generalisation task (NHPT) for the trained left hand after training completion. Priming with an excitatory repetitive transcranial magnetic stimulation as iTBS of either M1 or S1 can enhance motor learning across different sensorimotor abilities.